PERTUMBUHAN BENIH IKAN PATIN JAMBAL (Pangasius djambal) YANG DIBERIPAKAN DENGAN KADAR PROTEIN BERBEDA [The Growth of Pangasius djambal Fingerlings Fed with Different Dietary Protein Levels] - Ningrum Suhenda; Lies Setijaningsih; Yanti Suryanti (BERITA BIOLOGI, 2005)
The experiment was conducted to evaluate the growth of Pangasius djambal which were fed with different dietary protein levels.Fifteen fingerlings averaging 6.13 g individual body weight were stocked in each of 9 fibreglass tanks filled with 30 liters of water.They were fed daily for 42 days with diets containing 30%, 35% and 40 % protein. The feed was given in crumbled form at 7% of total biomass,4 times a day and contains 2600 k.cal.DE/kg feed.The result showed that feeds with different protein content gave qudratic respon curve. Maximum values for protein retention (36.65%) were obtained with feed containing 34.14 % protein.The feed with 35% protein content gave the lowest (78.12%) lipid retention. Feed conversion ratio (1.31-1.36), daily growth rate(3.64-3.82%) and protein efficiency ratio (2.05 - 2.29) were not different among treatments.The survival rates 100% were the same for all treatments.It is suggested that feed with protein content 35% and 2600 K. cal DE/ kg feed can be used in intensive culture of Pangasius djambal fingerlings to attain the best growth and suvival rate.